2018
DOI: 10.12688/f1000research.14476.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the higher incidence of tuberculosis among migrants and ethnic minorities in the UK

Abstract: Migrants and ethnic minorities in the UK have higher rates of tuberculosis (TB) compared with the general population. Historically, much of the disparity in incidence between UK-born and migrant populations has been attributed to differential pathogen exposure, due to migration from high-incidence regions and the transnational connections maintained with TB endemic countries of birth or ethnic origin. However, focusing solely on exposure fails to address the relatively high rates of progression to active disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 135 publications
2
31
1
9
Order By: Relevance
“…Our analysis emphasizes the value of focusing on country of birth and length of time in the United States to guide how to best expand LTBI testing and treatment. Other factors, such as underlying conditions and socioeconomic disparities, could play a role in TB risk (32). Accordingly, populations should be prioritized for TB testing according to their relative risk of being TB infected or having TB develop.…”
mentioning
confidence: 99%
“…Our analysis emphasizes the value of focusing on country of birth and length of time in the United States to guide how to best expand LTBI testing and treatment. Other factors, such as underlying conditions and socioeconomic disparities, could play a role in TB risk (32). Accordingly, populations should be prioritized for TB testing according to their relative risk of being TB infected or having TB develop.…”
mentioning
confidence: 99%
“…The TB prevalence and incidence rates in asylum seekers from Eritrea and Somalia in our study were much higher than the WHO-estimated TB incidence in Eritrea (74 cases/100,000 population) and in Somalia (270 cases/100,000 population) (8). A plausible explanation for this finding is the additional risk for infection while traveling to Europe, where overcrowding and unsanitary conditions are common along travel routes, on top of the baseline infection risk in the country of birth (15,16). Walker et al (17) found molecular and epidemiologic evidence for this in their study of a cluster of multidrug-resistant M. tuberculosis infections among patients arriving in Europe from the Horn of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid decline in TB incidence has been reported in countries that have established efficient TB control measures, such as China, Cuba, and Peru [18][19][20]. Non-Saudis showed a higher number of TB cases and rates compared to Saudis, which could be related to the high TB incidence rates in their countries [4,13,[21][22][23][24]. Although many non-Saudis may have LTBI, they acquired active TB during their residence in the KSA due to poor living conditions, e.g., poor housing, malnutrition, and work stress [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-Saudi females mostly came to the kingdom from high TB risk countries. Saudi males were reported at higher TB rates than females (twice), representing the significance of the social/communal responsibility of both genders [21,26]. Males are commonly more susceptible to TB than females because they have relatively wide-ranging social networks that increase their risk of TB infection [27,21], Moreover, smoking is more common in males and has a confirmed connection with TB [4,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%